SKELETAL MUSCLE METASTASES FROM CA LUNG - KUMPONPUNTH, Sopon; PEKANAN, Patchrin; PONGPECH, Sirintara (The ASEAN Journal of Radiology, 2023)
Metastatic nodule to the thigh muscle from carcinoma of the lung in a 57 year-old foreign male patient was presented. The nodule was seen faintly on TIWI axial MRI scan. The nodule was seen better by coronal view TIWI and axial view T2WI. Skeletal muscles are still considered rare sites for metastases.